UNDERSTANDING RESEARCH DYNAMICS IN ORGANIC FOOD CONSUMPTION BEHAVIOUR: A QUANTITATIVE STUDY - MIRUDULA A T,; DR. R INITHA RINA, (IJRDO - Journal of Business Management, 2025)
This study employs a bibliometric analysis to explore existing research on organic food consumption behavior and uncover prominent scholarly themes and emerging trends. A total of 428 articles published between 2014 and 2024 were retrieved from the Scopus database, and the analysis was conducted using the Bibliometrix R package and its Biblioshiny interface, focusing on research trends, keyword co-occurrence, and collaboration patterns. Results indicate a remarkable increase in systematic scientific interest has increased steadily over the decade, with peaks and troughs that are clearly affected by world events and changing research interests. Countries such as Italy, India, China, and the USA have led the way to be the biggest contributors to the research with significant citation impact and academic depth of engagement. Subsequent thematic analysis describes broad areas of concern in this field of research: food provision, consumer behaviour, sustainability, and the environment. The co-occurrence network captures strong connections between consumer behavior, marketing strategy, environmental sustainability, and food supply chains. Sustainability still commands a central role in the importance given to the values and themes of food markets. This study focuses on the point that consumer behavior, marketing, and environmental sustainability are all tightly bound and thus illustrates implications for future market strategies.